Moisture-cured UV (ultraviolet) adhesive as well as preparation method and application thereof

By modifying the photoinitiator containing hydroxyl groups, a moisture-cured UV glue was prepared. The dual curing mechanism of UV light and moisture was used to solve the problems of incomplete curing of UV glue and not oleic acid resistance, significantly improving the resistance to oleic acid and bonding strength.

CN119775908AActive Publication Date: 2025-04-08DONGGUAN APUBOND NEW MATERIAL TECH CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411984665.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

When existing UV glue is exposed to irregular parts or shaded areas formed by plug-ins, it is prone to incomplete curing and is not resistant to oleic acid, which affects the stability and durability of long-term use.

Method used

The photoinitiator containing hydroxyl groups was modified by γ-glycidyl ether oxysilpropylsesquioxane to prepare a moisture-cured UV glue, which consists of a modified photoinitiator, a silane-modified base polymer, diluent, filler, thixotropic agent, promoter, catalyst, etc. The curing degree and bonding strength are improved through the dual curing mechanism of UV light and moisture.

Benefits of technology

It significantly improves the oleic acid resistance and bonding strength of UV glue, shortens the UV curing time, ensures the complete curing of irregular special-shaped parts and shaded areas, and is also suitable for bonding of electronic products that are in contact with the human body for a long time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222288680000081
    Figure BDA0005222288680000081
  • Figure BDA0005222288680000091
    Figure BDA0005222288680000091
Patent Text Reader

Abstract

The invention belongs to the technical field of UV glue, and relates to moisture-cured UV glue as well as a preparation method and application thereof. The invention provides a moisture-cured UV (ultraviolet) adhesive which is prepared from the following raw materials in parts by mass: 100 parts of a silane modified base polymer, 10-40 parts of a diluent, 10-40 parts of filler, 5-10 parts of a thixotropic agent, 1-3 parts of an accelerant, 1-3 parts of a catalyst and 1-3 parts of a modified photoinitiator. According to the invention, gamma-glycidoxysilylpropyl sesquioxane is adopted to modify the photoinitiator containing hydroxyl to prepare the UV adhesive, and the UV adhesive has the advantages of excellent anti-oleic acid effect, short UV curing time and high shear strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of UV glue and relates to moisture-cured UV glue and a preparation method and application thereof. Background Art

[0002] UV light-curing adhesive (UV glue for short) refers to an adhesive that uses ultraviolet light as an energy source to irradiate photoinitiators to produce free radicals or cations and other active species, thereby initiating rapid polymerization and cross-linking reactions of oligomers or monomers to achieve curing. As the most common type of radiation-curing adhesive, UV glue has many advantages, such as no solvent, basically no pollution, energy saving and environmental protection, fast curing speed, which is conducive to automated production on high-speed production lines, fast positioning speed, high production efficiency, room temperature or low temperature curing, small size of curing equipment, high bonding strength, and applicability to a variety of substrates. It is widely used in precision industries such as electronics, optical components and biomedicine.

[0003] When conventional UV adhesives are used to bond irregular shaped parts or shadow areas formed by plug-in shielding, incomplete curing often occurs due to the difficulty of UV light to reach. Another solution is to compensate for this through dual curing technology. UV / moisture dual curing adhesives contain both photocurable groups (such as acrylates) and moisture-curable groups (isocyanates or siloxanes) in the photocurable resin. After UV light exposure, the photoinitiator initiates the polymerization of the acrylate group to achieve rapid light curing. Then, it is placed at room temperature, and the moisture in the air reacts with the isocyanate or siloxane group in the system to achieve slow post-curing, further improving the degree of curing and bonding strength. Moisture post-curing can improve the degree of curing in areas where UV light is insufficient, and at the same time does not require additional heating, saving energy and equipment. Therefore, it is welcomed by the market and is currently widely used in UV coating adhesives. Since moisture-cured UV adhesives are widely used in the bonding of electronic products that come into contact with the human body for a long time, such as headphones, it is necessary to examine and improve their oleic acid resistance. Summary of the invention

[0004] The purpose of the present invention is to provide a moisture-curing UV adhesive, which is intended to solve the technical problem that UV adhesive is not resistant to oleic acid, and to maintain or improve its basic properties of strength and drop resistance. To this end, the present invention provides a moisture-curing UV adhesive and its preparation method and application to solve this need in the art.

[0005] On the one hand, the present invention relates to a moisture-curing UV adhesive, which is composed of the following raw materials, measured by mass: 100 parts of a silane-modified base polymer, 10 to 40 parts of a diluent, 10 to 40 parts of a filler, 5 to 10 parts of a thixotropic agent, 1 to 3 parts of an accelerator, 1 to 3 parts of a catalyst, and 1 to 3 parts of a modified photoinitiator;

[0006] The silane-modified base polymer is a terminal reaction type liquid acrylic resin KANEKA XMAP TM ;

[0007] The preparation method of the modified photoinitiator comprises: mixing a photoinitiator containing hydroxyl group, γ-glycidyl ether silyl propyl sesquioxane, mercaptosuccinic acid and azobisisobutyronitrile in an organic solvent, reacting at 70-80° C. for 18-24 hours, immersing in water, standing and filtering to obtain the modified photoinitiator.

[0008] Furthermore, in the moisture-curing UV adhesive provided by the present invention, the molar ratio of the hydroxyl-containing photoinitiator, γ-glycidyloxysilylpropylsesquioxane, mercaptosuccinic acid and azobisisobutyronitrile is 10:3-5:2-4:1-3.

[0009] Furthermore, in the moisture-curing UV adhesive provided by the present invention, the diluent is at least one of 4-acryloylmorpholine, isobornyl acrylate, tetrahydrofuran acrylate, cyclotrimethylolpropane formal acrylate, ethoxyphenol acrylate, tripropylene glycol diacrylate, and neopentyl glycol dimethacrylate.

[0010] Furthermore, in the moisture-curing UV adhesive provided by the present invention, the filler is at least one of nano calcium carbonate, heavy calcium carbonate, talcum powder, and light calcium carbonate.

[0011] Furthermore, in the moisture-curing UV adhesive provided by the present invention, the thixotropic agent is fumed silica.

[0012] Furthermore, in the moisture-curing UV adhesive provided by the present invention, the accelerator is aminopropyltriethoxysilane.

[0013] Furthermore, in the moisture-curing UV adhesive provided by the present invention, the catalyst is dibutyltin dilaurate.

[0014] Furthermore, in the moisture-curing UV adhesive provided by the present invention, the hydroxyl-containing photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone and / or hydroxycyclohexane phenone.

[0015] Furthermore, in the moisture-curing UV adhesive provided by the present invention, the shear strength of the UV adhesive after curing is not less than 10 MPa.

[0016] On the other hand, the present invention relates to the use of the moisture-curing UV adhesive in the bonding of electronic components.

[0017] Compared with the prior art, the technical solution provided by the present invention has at least the following beneficial effects or advantages:

[0018] (1) Excellent anti-oleic acid effect: By modifying the hydroxyl-containing photoinitiator with γ-glycidyl ether silyl propyl sesquioxane, the obtained UV adhesive has significant anti-oleic acid performance. This is especially important for the bonding of electronic products that come into contact with the human body for a long time, such as headphones, to ensure the stability and durability of the product during use.

[0019] (2) Shorter UV curing time: The modified photoinitiator enables the UV glue to undergo polymerization and cross-linking reaction more quickly under ultraviolet radiation, thereby achieving rapid curing. This is conducive to improving production efficiency, especially in automated production on high-speed production lines.

[0020] (3) High shear strength: After curing, the moisture-curing UV adhesive provided by the present invention has a shear strength of not less than 10 MPa, which has high bonding strength. This ensures a firm connection between the bonded materials and improves the overall performance of the product.

[0021] (3) Dual curing mechanism: The UV adhesive contains both photocurable groups (such as acrylates) and moisture-curable groups (such as siloxanes), so it has UV / moisture dual curing properties. This can make up for the incomplete curing phenomenon when UV light is difficult to reach irregular shaped parts or shadow areas formed by plug-in shielding, further improving the degree of curing and bonding strength.

[0022] Due to the above advantages, the moisture-cured UV adhesive provided by the present invention has broad application prospects in precision industries such as electronic appliances, optical components and biomedicine. In particular, in the bonding of electronic components, it can exert excellent performance and effects. In summary, the technical solution provided by the present invention shows significant beneficial effects or advantages in terms of oleic acid resistance, UV curing time, shear strength, dual curing mechanism, energy saving and environmental protection, and application fields. DETAILED DESCRIPTION

[0023] The technical scheme of the present invention is described below in conjunction with the embodiments, but the present invention is not limited to the following embodiments. The experimental methods and detection methods described in each embodiment are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.

[0024] The silane-modified base polymer in the following examples is a terminal reaction type liquid acrylic resin KANEKAXMAP TM , purchased from Kaneka Co., Ltd.

[0025] The nano calcium carbonate in the following examples is calcium carbonate particles with a particle size of 100 to 200 nm.

[0026] The model of the fumed silica in the following examples is R972, purchased from Shanghai Haiyi Science and Technology Trading Co., Ltd.

[0027] The γ-glycidyloxysilylpropylsesquioxane in the following examples has a CAS number of 68611-45-0.

[0028] Example

[0029] This embodiment provides a method for preparing a moisture-curing UV adhesive.

[0030] Take a hydroxyl-containing photoinitiator, γ-glycidyl ether silyl propyl sesquioxane, mercaptosuccinic acid and azobisisobutyronitrile in a molar ratio of 10:3-5:2-4:1-3, add them to THF, and mix 50mL THF for every 1eq of hydroxyl-containing photoinitiator. Add to a 100mL three-necked flask through an addition funnel. Place the three-necked flask on a magnetic stirrer and stir to completely dissolve the drug in THF. The system is a colorless clear solution with slight heat release. Heat the oil bath to 75°C for 20 hours, drip the product into water, completely immerse the product and let it stand overnight, and filter to obtain a solid, which is the modified photoinitiator.

[0031] In parts by mass, take the silane-modified base polymer (terminal reaction type liquid acrylic resin KANEKAXMAP TM ) 100 parts, diluent 10-40 parts, filler 10-40 parts, thixotropic agent 5-10 parts, accelerator 1-3 parts, catalyst 1-3 parts and modified photoinitiator 1-3 parts.

[0032] Add silane-modified base polymer and octyl phthalate into a planetary mixer and stir at room temperature to obtain a mixed material. Add filler into the mixed material and stir at 90°C under vacuum to obtain a mixed material. After cooling to room temperature, quickly add thixotropic agent, accelerator, catalyst and modified photoinitiator, stir at 450r / min under vacuum for 30 minutes, and pack the material to obtain UV adhesive.

[0033] Test Case

[0034] This test example provides a performance test of UV adhesives with different compositions.

[0035] Referring to the preparation process of Example 1, different test groups were set up, as follows.

[0036] Test Group 1: It is composed of the following raw materials, in parts by mass: 100 parts of silane-modified base polymer, 10 parts of diluent (4-acryloylmorpholine), 10 parts of filler (nano-calcium carbonate), 5 parts of thixotropic agent (fumed silica), 1 part of accelerator (aminopropyltriethoxysilane), 1 part of catalyst (dibutyltin dilaurate) and 1 part of modified photoinitiator; the molar ratio of 2-hydroxy-2-methyl-1-phenyl-1-propanone, γ-glycidyloxysilylpropylsesquioxane, mercaptosuccinic acid and azobisisobutyronitrile in the modified photoinitiator is 10:3:2:1.

[0037] Test Group 2: It is composed of the following raw materials, in parts by mass: 100 parts of silane-modified base polymer, 12 parts of diluent (isobornyl acrylate), 25 parts of filler (nano-calcium carbonate), 7 parts of thixotropic agent (fumed silica), 2 parts of accelerator (aminopropyltriethoxysilane), 2 parts of catalyst (dibutyltin dilaurate) and 2 parts of modified photoinitiator; the molar ratio of hydroxycyclohexane phenone, γ-glycidyloxysilylpropylsesquioxane, mercaptosuccinic acid and azobisisobutyronitrile in the modified photoinitiator is 10:4:3:2.

[0038] Test Group 3: It is composed of the following raw materials, in parts by mass: 100 parts of silane-modified base polymer, 40 parts of diluent (isobornyl acrylate), 40 parts of filler (nano-calcium carbonate), 10 parts of thixotropic agent (fumed silica), 3 parts of accelerator (aminopropyltriethoxysilane), 3 parts of catalyst (dibutyltin dilaurate) and 3 parts of modified photoinitiator; the molar ratio of 2-hydroxy-2-methyl-1-phenyl-1-propanone, hydroxycyclohexane phenone, γ-glycidyloxysilylpropylsesquioxane, mercaptosuccinic acid and azobisisobutyronitrile in the modified photoinitiator is 5:5:5:4:3.

[0039] Comparative Group 1: This comparative group is the same as the experimental group 3, except that the photoinitiator is not modified by using γ-glycidyl ether silyl propyl sesquioxane.

[0040] Comparative group 2: This comparative group is the same as experimental group 3, except that the molar ratio of 2-hydroxy-2-methyl-1-phenyl-1-propanone, hydroxycyclohexane phenone, γ-glycidyloxysilylpropylsesquioxane, mercaptosuccinic acid and azobisisobutyronitrile in the modified photoinitiator is 5:5:10:4:3.

[0041] (1) Curing performance

[0042] The UV glue obtained from the experimental groups 1 to 3 and the comparative groups 1 to 2 was applied with a glue gun and then UV+moisture curing was performed at room temperature. The moisture curing conditions were uniformly cured at room temperature and 50±51% RH for 168h (one week). The test method was as follows:

[0043] 1. UV curing time: Place the test sample 10 cm below the light source and irradiate it with UV light intensity of 55 mW / cm 2 , until the sample surface is no longer sticky, and calculate the time required.

[0044] 2. Hardness: Test in accordance with GB / T 2411-2008 Plastics and hard rubber - Determination of indentation hardness (Shore hardness) using a hardness tester.

[0045] 3. Tensile strength and elongation at break: Test according to GB / T 30776-2014 Test method for tensile strength and elongation at break of adhesive tape.

[0046] 4. Shear strength: Tested in accordance with GB / T 7124-2008 Determination of tensile shear strength of adhesives (rigid material to rigid material).

[0047] The test results are shown in Table 1.

[0048] Table 1: Curing properties

[0049]

[0050] As shown in Table 1, after the photoinitiator is modified with γ-glycidyl ether silyl propyl sesquioxane, the UV curing time can be effectively shortened, and a higher hardness, tensile strength, elongation at break and shear strength can be obtained in a shorter period of light radiation, which greatly shortens the curing time. On the other hand, it can be seen from the comparison group 2 that when the addition amount of γ-glycidyl ether silyl propyl sesquioxane is too high, in addition to partially participating in the connection to improve the colloid strength, the excess part exists in the form of impurities, resulting in a longer UV curing time and a decrease in tensile strength.

[0051] (2) Drop resistance and oleic acid resistance

[0052] 1. Drop resistance: The cured test piece (PC / PC) is dropped from a height of 1 meter to a marble floor repeatedly until the bonding fails. The number of drops at failure is recorded. Each sample is tested 3 times and the average value is taken.

[0053] 2. Oleic acid resistance: The fully cured adhesive was immersed in 60°C oleic acid, taken out after 7 days, the bonding strength was tested, and the bonding strength retention rate was calculated.

[0054] Table 2: Drop resistance and oleic acid resistance

[0055]

[0056] As shown in Table 2, after the photoinitiator is modified with γ-glycidyl ether silyl propyl sesquioxane, the drop resistance and oleic acid resistance of the UV adhesive can be effectively improved, and it is suitable for improving the bonding performance of electronic products that come into contact with the human body for a long time.

[0057] The embodiments described above are part of the embodiments of the present invention, but not all of them. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but only represents selected embodiments of the present invention. All other embodiments obtained without creative work and related deductions and substitutions made by ordinary technicians in the field under the conditions of the concept of the present invention belong to the scope of protection of the present invention.

Claims

1. A moisture-curing UV adhesive, characterized in that: The invention is composed of the following raw materials in parts by mass: 100 parts of silane-modified base polymer, 10 to 40 parts of diluent, 10 to 40 parts of filler, 5 to 10 parts of thixotropic agent, 1 to 3 parts of accelerator, 1 to 3 parts of catalyst and 1 to 3 parts of modified photoinitiator; The silane-modified base polymer is a terminal reaction type liquid acrylic resin KANEKA XMAP TM ; The preparation method of the modified photoinitiator comprises: mixing a photoinitiator containing hydroxyl group, γ-glycidyl ether silyl propyl sesquioxane, mercaptosuccinic acid and azobisisobutyronitrile in an organic solvent, reacting at 70-80° C. for 18-24 hours, immersing in water, standing and filtering to obtain the modified photoinitiator.

2. The moisture-curing UV adhesive according to claim 1, characterized in that: The molar ratio of the photoinitiator containing hydroxyl group, gamma-glycidyl ether silyl propyl sesquioxane, mercaptosuccinic acid and azobisisobutyronitrile is 10:3-5:2-4:1-3.

3. The moisture-curing UV adhesive according to claim 1, characterized in that: The diluent is at least one of 4-acryloylmorpholine, isobornyl acrylate, tetrahydrofuran acrylate, cyclotrimethylolpropane formal acrylate, ethoxyphenol acrylate, tripropylene glycol diacrylate, and neopentyl glycol dimethacrylate.

4. The moisture-curing UV adhesive according to claim 1, characterized in that: The filler is at least one of nano calcium carbonate, heavy calcium carbonate, talcum powder and light calcium carbonate.

5. The moisture-curing UV adhesive according to claim 1, characterized in that: The thixotropic agent is fumed silica.

6. The moisture-curing UV adhesive according to claim 1, characterized in that: The accelerator is aminopropyltriethoxysilane.

7. The moisture-curing UV adhesive according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate.

8. The moisture-curing UV adhesive according to claim 1, characterized in that: The photoinitiator containing hydroxyl group is 2-hydroxy-2-methyl-1-phenyl-1-propanone and / or hydroxycyclohexane phenone.

9. The moisture-curing UV adhesive according to claim 1, characterized in that: The shear strength of the UV glue after curing is not less than 10 MPa.

10. Use of the moisture-curing UV adhesive according to any one of claims 1 to 9 in bonding electronic components.

Citation Information

Patent Citations

  • Silsesquioxane photoinitiators

    CN102232081A

  • UV-photocuring light guide adhesive and preparation method thereof

    CN107245302A

  • Preparation method of UV curable organosilicon resin for direct writing molding

    CN108264640A

  • UV-dampness double-curing system silane modified sealant and preparation method thereof

    CN108395858A

  • Polyfunctionality POSS (Polyhedral Oligomeric Silsesquioxane) modified light-cured resin and preparation method thereof

    CN108659471A